Utilization of Primary Healthcare Services and Stunting Among Children Aged 0-59 Months in Indonesia: A National Cross-Sectional Study - Apriliani Apriliani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Stunting remains a critical public health concern in Indonesia, contributing toelevated morbidity rates and undermining the quality of human capital. While primary healthcare services are central to preventive efforts, their direct association with stunting at the national scale remains inadequately explored. This study investigates the relationship between primary healthcare utilization and stunting incidence among children aged 0-59 months in Indonesia, using data from the 2023 Indonesia Health Survey (SKI). A cross-sectional analytical design was employed, involving 79,141 children after data cleaning. Nutritional status was measured via the height-for-age (H/A) indicator based on WHO Z-scores. Independent variables included child's sex, maternal education level, maternal employment status, residential area, availability of primary healthcare facilities, and health insurance ownership. Statistical analysis encompassed univariate, bivariate (chi-square test), and multivariate (binary logistic regression) methods. Significant associations were found for sex, maternal education, place of residence, and availability of healthcare facilities (p < 0.05), while maternal employment and health insurance showed no significant relationship. Multivariate analysis identified maternal education as the dominant determinant (p = 0.023; Exp(B) = 1.040; 95% CI: 1.006-1.077). Children of mothers with lower educational attainment faceda heightened risk of stunting compared to those whose mothers had higher education. Utilization of primary healthcare services was associated with stunting among children, particularly through maternal education as a key determinant. Findings underscore the importance of strengthening family-based interventions and enhancing maternal health literacy within the framework of primary healthcare to address stunting more effectively Keywords: Stunting, Children, Primary healthcare services, Indonesia